STUDI PENGGUNAAN TRUK COLT DIESEL 100 PS UNTUK PENGANGKUTAN BIBIT DALAM PEMBANGUNAN HUTAN TANAMAN INDUSTRI - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
This paper discribes the study of the use of Colt diesel 100 PS truck for seedling transportation in timber estate establishment carried out at one timber estate company in South Sumatera in 1991. The objective is to find out the information about the use of Colt Diesel 100 PS truck for seedling transportation. Data on productivity and cost of Colt Diesel 100 PS truck as weel as hauling distance and labor’s wages were collected. The study results are as follows :Colt Diesel 100 PS truck is appropriate for transporting seedling from plantation in timber estate area. To make loading and un;oading easy and to avoid the damage of seedling during transportation activity, the seedling should be put into strong wood boxes.Colt Diesel 100 PS truck can be loaded with 20 to 21 seedling boxes consisting of 1,200 to 1,260 seedlings. The productivity of Colt Diesel 100 PS truck for seedling transportation varied from 8,675 to 13,340 seedling-km/hour with an average of 10,944 seedling-km/hour.Cost of Colt Diesel 100 PS truck per seedling ranged between Rp. 3.20 and Rp 4.84/seedling-km with an average of Rp 3.87/seedling-km.To make seedling transportation activity runs well, it is suggested that forest roads be paved so that they can be used at all weather conditions.